Impact of work and working conditions on chronic low back pain among fisher women: a cross sectional study in Trivandrum - Abdul Rahim, Jazeela; Kannan, Srinivasan; Rajagopalan, Harini; Nafi, Muhammed (International Journal Of Community Medicine And Public Health, 2024)
Background: This study aimed to estimate the prevalence of chronic low back pain, its severity and associated factors among fisherwomen. Methods: Cross-sectional survey conducted among 336 fisherwomen aged 18-49 years from 7 fishing villages in Trivandrum. The prevalence of chronic low back pain estimated using Nordic body map. Pain severity was assessed using the pain numeric rating scale. Results: Prevalence of chronic low back pain was 45%. High BMI, UTI history, stress-induced headaches, falls, physical abuse, water-collection frequency, work-experience, and standing duration were associated with chronic low back pain. The pain severity prevalence was 23.8% mild, 51.65% moderate and 24.5% severe. Income, continuous-standing, improper-seating, and stipulated rest-time were associated with seventy of chronic low back pain. Standing continuously and improper seating were predictors of pain severity. Conclusions: Low back pain is common among fisherwomen contributed by work-related behavior. Posture correction measures such as educating the fisherwomen on appropriate posture and need for relaxation will improve their health conditions. Improved working environments which include proper resting place, designated space for vending with proper seating arrangement with chairs and with back support will improve the LBP status of fisherwomen.